Help‐seeking among psychiatrically hospitalized military personnel at risk for suicide. Issue 1 (11th November 2022) - Novak, Laura A.; LaCroix, Jessica M.; Perera, Kanchana U.; Stivers, Max; Schvey, Natasha A.; Goodie, Jeffrey L.; Olsen, Cara; Sbrocco, Tracy; Goldston, David B.; Soumoff, Alyssa; Weaver, Jennifer; Ghahramanlou‐Holloway, Marjan
Abstract: Introduction: Promoting help‐seeking is a key suicide prevention strategy. Yet, research on help‐seeking patterns by high‐risk individuals is limited. This study examined help‐seeking among United States military Service members admitted for psychiatric inpatient care. Methods: Participants were active duty Service members ( N = 111) psychiatrically hospitalized for a suicide‐related event. Data were collected as part of a larger randomized controlled trial. Reported types and perceived helpfulness of resources sought 30 days before hospitalization were examined. Hierarchical binary logistic regressions were used to examine associations among types of helping resources, mental health treatment stigma, and perceived social support. Results: Approximately 90% of participants sought help prior to hospitalization, most frequently from behavioral health providers and friends. Accessed resources were generally considered helpful. Adjusting for covariates, mental health treatment stigma was not associated with seeking help from any resource type. Higher perceived social support was associated with greater likelihood of help‐seeking from a friend (OR = 1.08, p = 0.013 [95% CI = 1.02, 1.14]). Marital status, education level, and organizational barriers were associated with specific types of resources, and/or not seeking help. Conclusion: Help‐seeking is a complex human behavior. Promoting help‐seeking among vulnerable subgroups requires further understanding of multiple interconnected factors.